PENDAMPINGAN PENYUSUNAN MODUL PELATIHAN BAHASA INGGRIS BERBASIS KOMPETENSI KERJA UNTUK FRONT OFFICE PERHOTELAN - Miqawati, Alfi Hidayatu; Fitri Wijayanti,; Cholimatus Zuhro,; Agus Setia Budi,; Nila Susanti, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The tourism and hospitality industry relies heavily on human resources. One of the competencies required is mastery of the ability to communicate using English. This article aims to describe the process of assisting in the preparation of competency-based training modules. The activity implementation method was divided into three stages, namely planning, implementation and evaluation. Activity planning included follow-up surveys, determining schedules, and preparing instruments. Implementation of the activities began with the socialization of regulations and documents related to front office competency certification in the hospitality sector, preparation of training modules, and assistance with the preparation of modules. Evaluation of activities was carried out by analyzing modules and partner satisfaction. This activity is very helpful for partners and in the future, there will be similar assistance for the development of other modules.